Peripersonal Space and Bodily Self-Consciousness: Implications for Psychological Trauma-Related Disorders - Rabellino, Daniela; Frewen, Paul A.; McKinnon, Margaret C.; Lanius, Ruth A. (Frontiers in Neuroscience, 2020)
Peripersonal space (PPS) is defined as the space surrounding the body where we can reach or be reached by external entities, including objects or other individuals. PPS is an essential component of bodily self-consciousness that allows us to perform actions in the world (e.g., grasping and manipulating objects) and protect our body while interacting with the surrounding environment. Multisensory processing plays a critical role in PPS representation, facilitating not only to situate ourselves in space but also assisting in the localization of external entities at a close distance from our bodies. Such abilities appear especially crucial when an external entity (a sound, an object, or a person) is approaching us, thereby allowing the assessment of the salience of a potential incoming threat. Accordingly, PPS represents a key aspect of social cognitive processes operational when we interact with other people (for example, in a dynamic dyad). The underpinnings of PPS have been investigated largely in human models and in animals and include the operation of dedicated multimodal neurons (neurons that respond specifically to co-occurring stimuli from different perceptive modalities, e.g., auditory and tactile stimuli) within brain regions involved in sensorimotor processing (ventral intraparietal sulcus, the ventral premotor cortex), interoception (insula), and visual recognition (lateral occipital cortex). Although the defensive role of the PPS has been observed in psychopathology (e.g., in phobias) the relation between PPS and altered states of bodily consciousness remains largely unexplored. Specifically, PPS representation in trauma-related disorders, where altered states of consciousness can involve dissociation from the body and its surroundings have not been investigated. Accordingly, we review here: 1) the behavioral and neurobiological literature surrounding trauma-related disorders and its relevance to PPS; and 2) outline future research directions aimed at examining altered states of bodily self-consciousness in trauma related-disorders.